Computational study of quercetin effect on pre-apoptotic factors of Bad, Bak and Bim - Javad Saffari-Chaleshtori; Ehsan Heidari-Soreshjani; Majid Asadi-Samani (Shahrekord University of Medical Sciences, 2016)
Introduction: Quercetin is an effective compound which is found in many medicinal plants. Quercetin antioxidant properties against cancerous tumors and apoptosis induction have been demonstrated. This study is aimed to investigate the molecular dynamics of quercetin with regard to activating the pre-apoptotic factors such as Bim, Bak, and Bad using simulation software.Methods: In this study, the thermodynamic properties of flavonoid molecule of quercetin on three important factors in apoptotic pathway such as Bim, Bak, and Bad were investigated. After the three-dimensional structure of these molecules was obtained from NCBI and simulation was done by Gromacs software, docking stages were performed by AutoDock software and then the molecular dynamics of the complexes were investigated by Gromacs software.Results: The number of hydrogen bonds between quercetin and Bad was higher than Bak and Bim, which causes Bad to have lower energy than Bak and Bim. Mean root-mean-square deviation at 10 ns of simulation increased for Bad and Bak and decreased for Bim in quercetin presence. Root-mean-square fluctuation investigations indicated that Bim had the highest flexibility in quercetin presence compared to free state.Conclusion: Computational studies indicated that quercetin could have a greater effect on Bad compared to Bak and Bim. However it is necessary to investigate the effect mechanism of quercetin on these three pre-apoptotic factors in experimental studies.